Pruning Techniques in Łukasiewicz Logics - Basbous, Raed; Nagy, Benedek; Tajti, Tibor (Budapest Tech, 2025)
Short circuit evaluations and related pruning techniques play important roles in logic, artificial intelligence and computer science, especially, in software engineering, decision-making and hardware design. Here, we consider a well-known and widely applied fuzzy logic system, the & Lstrok;ukasiewicz logic. We present and prove various pruning techniques to make the evaluations of logical formulas faster and more efficient, by cutting those branches of the formula tree that have no influence on the result at the root. Complex examples show the efficiency of our pruning techniques, which are used to do the evaluation of formulas faster in & Lstrok;ukasiewicz logic. This logic is appropriate for various engineering applications related to fuzzy technology and decision making; therefore, our results are important for fast evaluation.
Keywords: many valued and fuzzy logics; fuzzy decision; generalized alpha-beta pruning; short-circuit evaluation; cuts off of expression trees